Silver nanoparticles induced alterations in multiple cellular targets, which are critical for drug susceptibilities and pathogenicity in fungal pathogen (Candida albicans) - Radhakrishnan VS (Dove Medical Press, 2018)
Venkatraman Srinivasan Radhakrishnan,1,2 Mohana Krishna Reddy Mudiam,3 Manish Kumar,1,2 Surya Prakash Dwivedi,4 Surinder Pal Singh,5 Tulika Prasad1,2 1Advanced Instrumentation Research and Facility (AIRF), Jawaharlal Nehru University (JNU), New Delhi, Delhi, India; 2Special Centre for Nano Sciences (SCNS), Jawaharlal Nehru University (JNU), New Delhi, Delhi, India; 3Analytical Chemistry Lab, Council for Scientific and Industrial Research (CSIR)-Indian Institute of Toxicology Research (IITR), Lucknow, Uttar Pradesh, India; 4School of Biotechnology, IFTM University, Moradabad, Uttar Pradesh, India; 5CSIR-National Physical Laboratory (NPL), New Delhi, Delhi, India Purpose: A significant increase in the incidence of fungal infections and drug resistance has been observed in the past decades due to limited availability of broad-spectrum antifungal drugs. Nanomedicines have shown significant antimicrobial potential against various drug-resistant microbes. Silver nanoparticles (AgNps) are known for their antimicrobial properties and lower host toxicity; however, for clinical applications, evaluation of their impact at cellular and molecular levels is essential. The present study aims to understand the cellular and molecular mechanisms of AgNp-induced toxicity in a common fungal pathogen, Candida albicans. Methods: AgNps were synthesized by chemical reduction method and characterized using UV–visible spectroscopy, X-ray powder diffraction, transmission electron microscopy, scanning electron microscopy–energy dispersive X-ray spectroscopy, energy dispersive X-ray fluorescence, and zeta potential. The anti-Candida activity of AgNps was assessed by broth microdilution and spot assays. Effects of AgNps on cellular and molecular targets were assessed by monitoring the intracellular reactive oxygen species (ROS) production in the absence and presence of natural antioxidant, changes in surface morphology, cellular ultrastructure, membrane microenvironment, membrane fluidity, membrane ergosterol, and fatty acids. Results: Spherical AgNps (10–30 nm) showed minimum inhibitory concentration (minimum concentration required to inhibit the growth of 90% of organisms) at 40 µg/mL. Our results demonstrated that AgNps induced dose-dependent intracellular ROS which exerted antifungal effects; however, even scavenging ROS by antioxidant could not offer protection from AgNp mediated killing. Treatment with AgNps altered surface morphology, cellular ultrastructure, membrane microenvironment, membrane fluidity, ergosterol content, and fatty acid composition, especially oleic acid. Conclusion: To summarize, AgNps affected multiple cellular targets crucial for drug resistance and pathogenicity in the fungal cells. The study revealed new cellular targets of AgNps which include fatty acids like oleic acid, vital for hyphal morphogenesis (a pathogenic trait of Candida). Yeast to hypha transition being pivotal for virulence and biofilm formation, targeting virulence might emerge as a new paradigm for developing nano silver-based therapy for clinical applications in fungal therapeutics. Keywords: AgNps, nanomedicine, drug resistance, membrane fluidity, antifungals, reactive oxygen species, ROS